2011
DOI: 10.1016/j.jconrel.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of inorganic nanocrystals into PLGA microsphere vaccines enables their intracellular localization in dendritic cells by electron and fluorescence microscopy

Abstract: Biodegradable poly-(D,L-lactide-co-glycolide) microspheres (PLGA-MS) are approved as a drug delivery system in humans and represent a promising antigen delivery device for immunotherapy against cancer. Immune responses following PLGA-MS vaccination require cross-presentation of encapsulated antigen by professional antigen presenting cells (APCs). While the potential of PLGA-MS as vaccine formulations is well established, the intracellular pathway of cross-presentation following phagocytosis of PLGA-MS is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…Collectively, our data support the conclusions of (Schliehe et al, 2011) who found that larger PLGA MPs remained in LAMP 1-positive lysosomes in dendritic cells and macrophages for at least two days after phagocytosis. They provided indirect evidence that ovalbumin encapsulated in the MPs was able to enter the cytoplasm of these cells and could activate the endoplasmic reticulum based MHC-1 pathway of antigen presentation to CD8+ T cells ('cross-presentation').…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Collectively, our data support the conclusions of (Schliehe et al, 2011) who found that larger PLGA MPs remained in LAMP 1-positive lysosomes in dendritic cells and macrophages for at least two days after phagocytosis. They provided indirect evidence that ovalbumin encapsulated in the MPs was able to enter the cytoplasm of these cells and could activate the endoplasmic reticulum based MHC-1 pathway of antigen presentation to CD8+ T cells ('cross-presentation').…”
Section: Discussionsupporting
confidence: 92%
“…These studies relied on light microscopy immunofluorescence analyses and another EM study reached the same conclusion (Mathiowitz et al, 1997). In contrast, (Schliehe et al, 2011) concluded that in dendritic cells, PLGA MPs remained in phago-lysosomes for many days. Given these contradictory results we wanted to establish more definitively here whether or not PLGA NPs of different sizes remain long-term in membrane-enclosed phagocytic/endocytic compartments, or whether they are able to disrupt the enclosing membrane and escape into the cytoplasm.…”
Section: Introductionmentioning
confidence: 92%
“…The HLA-A*0201-restricted peptide ELAGIGILTV (derived from the melanoma-associated differentiation antigen Melan-A/MART-1; A to L substitution at position 2 compared with its natural counterpart for higher immunogenicity and referred to as MART-1 [27][28][29][30][31][32][33][34][35] ), as well as the peptide labeled with a COOH-terminus FITC fluorochrome were produced by the Keck Facility (Yale University).…”
Section: Peptide and Cell Lines Peptidementioning
confidence: 99%
“…The human CD8 + T-cell receptor transgenic cell line DMF5, reactive with both the MART-1 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and MART-1 (27L- 35) epitopes, was kindly provided by John R Wunderlich, Surgery Branch, National Cancer Institute. This line, originally derived from a high avidity tumor-infiltrating lymphocyte clone that mediated tumor regression clinically, has been extensively described previously.…”
Section: Ctl Clonementioning
confidence: 99%
See 1 more Smart Citation